2012
DOI: 10.1242/jeb.069849
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic cod (Gadus morhua L.) in situ cardiac performance at cold temperatures: long-term acclimation, acute thermal challenge and the role of adrenaline

Abstract: SUMMARYThe resting and maximum in situ cardiac performance of Newfoundland Atlantic cod (Gadus morhua) acclimated to 10, 4 and 0°C were measured at their respective acclimation temperatures, and when acutely exposed to temperature changes: i.e. hearts from 10°C fish cooled to 4°C, and hearts from 4°C fish measured at 10 and 0°C. Intrinsic heart rate (f H ) decreased from 41beatsmin -1 at 10°C to 33beatsmin -1 at 4°C and 25beatsmin -1 at 0°C. However, this degree of thermal dependency was not reflected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 76 publications
3
17
1
1
Order By: Relevance
“…In the muscle itself, there can be changes in ion channel function (McArdle and Johnston, 1982;Godiksen and Jessen, 2002) as well as changes in muscle fibre protein composition (Johnston and Temple, 2002;Tattersall et al, 2012) and recruitment order (Rome, 1990;Catalán et al, 2004). At a physiological level, there are also changes in cardiac function (Keen and Farrell, 1994;Lurman et al, 2012). These factors combined lead to maintained swimming performance despite changes in temperature, and thus maintained ability to out-swim predators or catch prey.…”
Section: Discussionmentioning
confidence: 99%
“…In the muscle itself, there can be changes in ion channel function (McArdle and Johnston, 1982;Godiksen and Jessen, 2002) as well as changes in muscle fibre protein composition (Johnston and Temple, 2002;Tattersall et al, 2012) and recruitment order (Rome, 1990;Catalán et al, 2004). At a physiological level, there are also changes in cardiac function (Keen and Farrell, 1994;Lurman et al, 2012). These factors combined lead to maintained swimming performance despite changes in temperature, and thus maintained ability to out-swim predators or catch prey.…”
Section: Discussionmentioning
confidence: 99%
“…The above changes all contribute to cardiac contractility and how it is maintained at low temperatures. Supporting this idea, Graham and Farrell (Graham and Farrell, 1989) demonstrated that maximum cardiac work is similar for rainbow trout acclimated to 5 or 15°C, and Lurman et al (Lurman et al, 2012) found little difference in the cardiac output of Atlantic cod acclimated to either 10 or 0°C measured at the respective acclimation temperature. Still missing from a full understanding of this cardiac compensatory mechanism is the connection between the necessary molecular-and protein-level changes induced by cold acclimation and the resultant changes in whole heart function.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies utilizing in situ cardiac preparations for studies of teleost fish set input pressure close to 0 for baseline conditions (Graham and Farrell, 1989;Farrell et al, 1996;Mendonça et al, 2007). It should be noted that systolic pressure (output pressure) was not set at a constant as in previous in situ work (Graham and Farrell, 1990;Farrell et al, 1996;Lurman et al, 2012), rather the diastolic and systolic pressures were measured inside the ventricle after changes in balloon volumes. The systolic pressures that were measured at baseline conditions were within the range of those that were used in previous in situ studies that controlled output pressures.…”
Section: Measurement Of Ventricular Pressure Generation Using Langendmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, given that temperature has a profound effect on numerous aspects of cardiac metabolic demand and perfusion (35), and that no data exist on the effects of temperature on q Cor or resistance, these experiments were performed at several acclimation temperatures (1, 5, and 10°C). These temperatures were chosen because we know very little about the cardiovascular physiology of nonpolar species at cold temperatures, and this is presently a focus in our laboratory (e.g., 59, Costa IASF, Hein TW, Secombes CJ, and Gamperl AK; unpublished observations).…”
mentioning
confidence: 99%